The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3136/fstr.10.93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mannooligosaccharides from Coffee Mannan on Fecal Microflora and Defecation in Healthy Volunteers

Abstract: Mannooligosaccharides (MOS) were purified from the thermally hydrolyzed mannan in spent coffee grounds, with the aim of achieving the full utilization of natural unused food material. The effects of MOS on fecal microflora and the defecating conditions in eight healthy volunteers were investigated. The subjects were administered MOS at 1.0 g/day and 3.0 g/day for 2 weeks. A 2 week interval was observed between the two dose intake periods. The content of Bifidobacterium significantly increased during the two pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 9 publications
(11 reference statements)
2
16
0
Order By: Relevance
“…Immunological effects of nondigestible oligosaccharides, such as fructooligosaccharides (FOS), 2,3) galactooligosaccharides, 4) and raffinose, 5) have been demonstrated. Recently, our studies have revealed that mannooligosaccharides (MOS) from coffee mannan improves the intestinal environment 6,7) by increasing Bifidobacterium. 8,9) MOS are mannosebased oligosaccharides with β-1, 4 linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological effects of nondigestible oligosaccharides, such as fructooligosaccharides (FOS), 2,3) galactooligosaccharides, 4) and raffinose, 5) have been demonstrated. Recently, our studies have revealed that mannooligosaccharides (MOS) from coffee mannan improves the intestinal environment 6,7) by increasing Bifidobacterium. 8,9) MOS are mannosebased oligosaccharides with β-1, 4 linkages.…”
Section: Introductionmentioning
confidence: 99%
“…1) Previous studies have revealed that MOS can promote the growth of bifidobacteria in the intestines and improve the fecal characteristic on human subjects. 2) We have recently been investigating alternative physiological functions of MOS from various perspectives. Asano et al reported the result of their long-term clinical study on human subjects: A daily intake of a 300 ml drink containing MOS (1 or 2 g/100 ml) lowered the level of abdominal and subcutaneous fat when administered everyday for twelve weeks.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Further investigations have been undertaken to explore the potential functionality of MOS. The liquid coffee beverage containing 3.0 g/day of MOS, assisted in reducing the areas of subcutaneous and visceral fat in somewhat overweight adults when consumed for 12 weeks.…”
Section: Introductionmentioning
confidence: 99%